The Personal Sources of Responsiveness. Introduction to a Special Section. Issue 1 (16th February 2020) - Campbell, Rosie; Zittel, Thomas
Abstract: Responsiveness is a core value in democratic politics. Individual legislators are important mechanisms for implementing this concern in real‐world settings and thus facilitating responsive government. This introduction to the special section on this topic starts out by highlighting the special relevance of individual legislators in this regard and by sketching important theoretical considerations that emerge from the political science literature on this issue. In its main part, it summarizes the key findings of the contributions in relation to its main theme, namely the personal sources of responsiveness. We end with a short conclusion that reflects on possible tensions between responsiveness and the personalization of representative systems.